The Effect of Core Competencies as a Moderator between Perceived Value and Destination Image in Green Hotel: An Assessment using Structural Equation Modeling Technique with Partial Least Square (i.e. PLS-SEM). - Rasidah Hamid; Intan Rahayu Abdul Razak; Noorazlin Ramli; Zurinawati Mohi; Nik Alif Amri Nik Hashim; Zurena@Rena Shahril; Zaliha Zainuddin; Nor Maizana Mat Nawi (International Journal of Supply Chain Management, 2020)
Abstract— This study was conducted to evaluate the effect of moderating factor namely Core Competencies on the relationship between the perceived Value and Destination Image among green hotel customers in Malaysia. This quantitative research was performed using a survey method through questionnaires. The total of 450 samples selection of data from guests who stayed in Malaysia certified green hotels were collected.  The results of the Structural Equation Modeling technique with Partial Least Square (i.e. PLS-SEM) revealed that the Core Competencies was found to have significant and positive moderator effect on the relationship between the perceived Value and Destination Image. Moreover, the effect of Perceived Value toward Destination Image was stronger, when the impact of Core Competencies is strong, as compared to the situation when Core Competencies is low, which is the effect of Perceived Value toward Destination Image tends to reduce. This study suggested that Green hotel investment for the development of core competencies in green segments was helpful to hotel industry for the enhancement of perceived value and destination image. Keywords—Moderator effect; core Competencies; perceived value; destination image; partial least square (PLS-SEM)